Sex differences and the effects of sex hormones on the structure of the corpus callosum - Khan, Irum Nawaz (2012)
OBJECTIVE This thesis examines sex differences in the structural properties of the corpus callosum (CC) during adolescence and investigates the possible role of sex hormones in the development of these sex differences, as well as hormonal effects on the inter-individual variations in the structure of the CC in young women.